Central Algarve karst system tufa-related dynamics, Portugal. - Guerreiro, Paulo (2017)
Geomorphological mapping is a powerful instrument improving the geomorphological interpretation and understanding of the processes and forms used in landscape studies, with the ability of organizing different thematic layers in the same map. The presented map provide relevant information about the different geomorphological units of the central Algarve (i.e. the Carboniferous flysch mountains; the Barrocal, with marly and karstified subunits), where a karst system is prominent. Solution karst morphologies and large dry areas are common in the elevated areas of the Barrocal, suggesting deep circulation of groundwater. These recharge areas feed the perched aquifers of the area, where discharge is controlled by the impervious lithologies (clay-rich strata of the turbidites, marls and argilites) in the valley bottoms or other leaks in dammed aquifers. In springs related to the main aquifers tufa are actively being formed and, close coupled to spring location, different tufa depositional systems develop.